What Happened to You? Conversations on Trauma, Resilience, and Healing - Winfrey, Oprah and Bruce D. Perry read by the Authors (New York Macmillan Audio, 2021)
Through wide-ranging and often deeply personal conversation, Oprah Winfrey and Dr Perry explore how what happens to us in early childhood ? both good and bad - influences the people we become. They challenge us to shift from focusing on 'What?s wrong with you?' or 'Why are you behaving that way?' to asking 'What happened to you?'. This simple change in perspective can open up a new and hopeful understanding for millions about why we do the things we do, why we are the way we are, providing a road map for repairing relationships, overcoming what seems insurmountable, and ultimately living better and more fulfilling lives.
Keywords: General; Developmental / General